Curvularia nelumbonicola (Pleosporaceae, Pleosporales), a new endophytic fungus from Thailand - Lapmak, Kodchakorn; Kumla, Jaturong; Phookung, Kotcharat; Suwannarach, Nakarin (Phytotaxa, 2025)
A new species of endophytic fungus, described herein as Curvularia nelumbonicola, was isolated from the leaves of lotus (Nelumbo nucifera Gaertn.) collected in Uttaradit Province, Thailand. This species is described using morphological characteristics and multi-gene molecular analyses. Morphologically, C. nelumbonicola is similar to C. chonburiensis and C. pisi, but it can be distinguished by its mostly shorter conidiophores. Multi-gene phylogenetic analyses based on a combination of the internal transcribed spacer (ITS) region of ribosomal DNA, glyceraldehyde-3-phosphate dehydrogenase (GAPDH), and translation elongation factor 1-alpha (TEF1) genes revealed that C. nelumbonicola forms a monophyletic clade and is clearly distinct from C. chonburiensis and C. pisi as well as other Curvularia species. A full description, illustrations, and a phylogenetic tree showing the position of C. nelumbonicola are provided.